Effects of Natural Products on ABCB1 Transporter in Rat Everted Gut - Maryam H. Shubbar; Omar A. Fadhil; Hussam H.Kadhum (Migration Letters, 2023)
ATP-binding Cassette (ABC) efflux transporters affect many of drug absorption. These efflux transporters limit the availability of a wide range of substances and especially cancer treatment medications. The effect of Curcumin and Panax ginseng on ABCB1 efflux activity was determined by measuring two ABCB1 substrates, verapamil and tamoxifen permeability in rat everted gut. The concentrations of absorbed verapamil and tamoxifen were measured by HPLC in the existence or not of Curcumin and Panax ginseng at variable time points (5, 15, 30, 45 and 60 min) by everted gut sacs model. At 60 min incubation, the permeability of verapamil in presence of tamoxifen, Curcumin and Panax ginseng was significantly (p≤0.001) increased by 2, 1.8 and 1.6- fold, respectively. Additionally, the concentration of tamoxifen that passed through the intestine wall elevated significantly (p≤0.001) when it was incubated with verapamil Curcumin and Panax ginseng by 1.8, 1.6 and 1.5-fold, respectively. This is the first study that established the supressing effect of Curcumin and Panax ginseng on gastrointestinal tract -ABCB1 transporter activity.